Hands-On and Virtual Laboratories in Electronic Circuits Learning—Knowledge and Skills Acquisition - Christos Tokatlidis; Sokratis Tselegkaridis; Sophia Rapti; Theodosios Sapounidis; Dimitrios Papakostas (Information)
Hands-on and virtual laboratory-based learning has been integrated into science education due to its potential positive impact on students’ knowledge and skills development. In this study, we explore the effect of the hands-on and virtual laboratories on 152 undergraduate students’ conceptual knowledge, inquiry, and measurement skills acquisition in the domain of operational amplifiers (op-amps) circuit learning. Students were divided into two groups and performed individually three experimental exercises involving basic op-amps electronic circuits: students in the Hands-On group performed the exercises in a physical laboratory environment, while students in the Virtual group performed the exercises in a virtual environment with TINA-TI (v9) software. Pre-post tests were used to quantify student performance progress stemming from their laboratory-type activities. Based on our findings, knowledge was developed the most, followed by inquiry skills, and finally, skills related to measuring electronic current quantities in a circuit, F(2,456) = 44.183, p = 0.000. Additionally, an ANCOVA analysis comparing the means of the three exercises revealed that the group participating in hands-on activities outperformed the group engaged in virtual activities, F(1,152) = 9.039, p = 0.003. Finally, we recommend designing a curriculum that focuses on both cognitive growth and skills development in the domain of op-amps.